Controlling Consumers in the Event of Future Wars - Enke, Stephen (Quarterly Journal of Economics, 1958)
I. Introduction, 558. — II. Some alternative wars and their economic impacts, 558. — III. Alternative suggestions for an over-all expenditure ration, 563. — IV. A pessimistic but realistic program, 569. — V. Concluding comment, 572.